Genetic structure and microsatellite-based genetic variation influenced by habitat fragmentation in pudu deer (Pudu puda) from southern Chile - Nelson Colihueque; Alberto Gantz (Neotropical Biology and Conservation, 2025)
Landscape alterations have strong impacts on the distribution of genetic variation within and between populations, and understanding these effects can provide insights for design conservation strategies. We analyzed 20 georeferenced individuals of pudu deer (Pudu puda) of three populations from southern Chile to obtain genetic diversity and distance parameters based on five polymorphic microsatellite loci. The genetic population structure was assessed by using STRUCTURE 2.3.4 and the effective population sizes (Ne) with NeEstimator 2.0 software. Habitat fragmentation metrics were also analyzed to correlate these data with the genetic variation focused to assess the effect of native forest fragmentation on the genetic structure of pudu deer. The mean number of alleles ranges from 2.8 to 4.2, while the mean number of private alleles ranged from 0.4 to 1.2. The mean observed heterozygosity ranged from 0.423 to 0.547. All populations displayed significant deficits of heterozygotes (FIS = 0.091-0.189, P < 0.0001). The FST on the whole populations and loci was low (mean FST = 0.0942) and without statistical significance (P > 0.05), indicating no genetic differentiation among populations. The STRUCTURE analysis did not reveal a population structure, and the NeEstimator found a markedly low Ne in a population compared to other analyzed populations. Multiple regression analysis indicates that two fragmentation metrics, namely, the proportion of the landscape covered by forest (PLAND) and the patch density (PD), negatively and significantly affected the number of alleles per locus as well as the observed heterozygosity (PLAND, β = -0.8740, P < 0.05; PD, β = -0.6594, P < 0.05). This result suggests that a greater degree of habitat fragmentation contributes to a decrease in genetic variation of pudu deer. Therefore, maintaining the native forest continuity across the distribution range of pudu deer could contribute to preserving the genetic diversity, enhancing the long-term survival of this mammal.